Assessment of suitability evaluation for Ficus altissima blume ancient trees in different climatic environments in Guangxi, China - Gu, Hongliang; Chen, Yuxia; Zhang, Qinqin (Frontiers in Plant Science, 2025)
IntroductionThe Guangxi Zhuang Autonomous Region of China is home to numerous Ficus altissima Blume (F. altissima) ancient trees over 300 years old, which hold significant cultural, ecological, and scientific research value. However, little is known about their current and future distribution suitability or growth trends. MethodsTo address this gap, using machine learning and species distribution models, we analyzed their distribution patterns and habitat suitability changes under current and future climate scenarios, incorporating 33 climatic, topographic, and soil-related driving factors.ResultsOur findings reveal that the region hosts 514 ancient F. altissima trees aged over 300 years, 114 of which exhibit declining or endangered growth conditions. The spatial distribution of these trees is highly discrete, influenced by topographical constraints and intraspecific competition. Over 45% are found at elevations between 80 and 150 meters. Jackknife analysis identified the mean temperature of the wettest quarter (bio8) as the most critical factor affecting their distribution (77.6% cumulative contribution when combined with temperature seasonality, bio4). Specifically, regions with bio8 < 26°C and bio4 > 625°C are unsuitable for F. altissima (LOV < 0.085). Additionally, tree size varies by habitat due to competition, with ancient trees in flat areas exhibiting larger average crown widths. The accuracy of the Maxent model is superior to models such as BIOCLIM and GLM. Compared to current, under the SSP1-2.6 and SSP5-8.5 climate scenarios, the moderately suitable distribution area expanded by 1.47% and 0.89%, respectively (averaging 5.53% across four time periods), while the highly suitable area decreased by 0.04% and 0.21%. These results provide valuable insights for the conservation and sustainable utilization of ancient F. altissima trees.